Estrus Cycle Monitoring System in Cow Based on IoT - Saputra, Mohammad Wahyu Denys; Anshori, Moh. Abdullah; Imammuddien, Azam Muzakhim (Jurnal Jaringan Telekomunikasi, 2023)
The orientation of local cattle farms generally only aims to take cow's milk, so local farmers do not have bulls and only have female cows to milk them. If a cow gives birth to a bull, the bull will be sold. This creates a separate problem for these farms because without a bull, the female cows cannot be fertilized naturally and can only be fertilized through artificial insemination so that the number of cows on the farm does not decrease and run out. However, this artificial insemination can only be given when a cow is in heat and cannot be done at any time. However, there are many ordinary dairy farmers in Indonesia who often lack knowledge about the signs of cow lust, making them run out of time for cow lust. Therefore, a device is made that can monitor the heat condition of cows on farms by using an infrared temperature sensor that is connected via the internet network and can be accessed via a smartphone, which can be monitored anytime and anywhere to help cattle breeders. The results of the implementation show that the performance of the infrared temperature sensor is very good because the measurement results are quite accurate because the accuracy level reaches 99.529 percent. The performance of the color sensor is also very good because it can detect colors accurately. The average delay obtained is 1.0175975 seconds. Meanwhile, the packet loss value obtained during the test was 16.11%.